Autorégulation, rapport à l'écrit et performance : analyse d'une activité rédactionnelle en français langue étrangère à l'université - Nada Najjar
This work is part of a two-phase study, which analyzes a typed writing task, attempts via video capture software. Our sample consists of 32 students from different profiles, including adults returning to studies, repeat students and new incoming students. Analysis of the video recordings describing the processual course of the writing activity in real time (30 minutes) allowed us to note a relationship between the number and type of writing pauses taken, the relation to writing, the experience of the students and their performance. The results show a high link between the student's writing performance and the strategies they use to manage their writing. In addition, a constructive relation to writing seems to facilitate an effective management of the editorial processes by systematically alternating planning (outlining) and other revision steps. In addition to their good performances in writing, adults returning to studies seem to better master their editorial (writing) activity, compared to novices. In sum, following our results, we suggest three ways of procedures favorable to the appropriation of an academic literacy: the representational (relation to writing), the procedural (editorial management) and the automation (related to competence).